Decision-Making Regarding the Continuation of Contraceptive Implant within 1 Year of Childbirth: A Comparison between Adolescents Receiving Individual Counseling through Print Media and Adolescents Receiving Video-Based Group Counseling - Teerapan Seehanantawong; Siriya Kitiyodom (The Royal Thai College of Obstetricians and Gynaecologists, 2021)
Objectives: To compare the continuation rates of contraceptive implant within 1 year of childbirth between adolescents receiving individual counseling through educational brochures and adolescents receiving video-based group counseling.Materials and Methods: This research was a prospective study of non-inferior trials in 272 postpartum adolescent mothers which compared between individual counseling and video-based group counseling. The video was created with introductory content about all methods of contraception including their advantages and side effects. The decision-making regarding the continuation of contraceptive implant usage would then be followed-up within 1 year. Criterion for non-inferiority was at a lower limit of < -7% for the 95% confidence interval (CI). Results: The adolescent mothers in this study were at the average age of 17 years old, and most of them were living with their husbands. The follow-up found that the decision rates of continuing the use of contraceptive implants comparing between those who received video-based group counseling and individual counseling at 6 months were 77% and 72.8% (95% CI = -5.8, 14.2), at 1 year were 69.4% and 65.0% (95% CI = -6.4, 15.3), with the lower confidence limit being inside the non-inferiority limit of -7%. It can be interpreted that video-based group counseling was not less effective than individual counseling at 6 months and 1 year.Conclusion: Evidence of non-inferiority was noted comparing individual counseling and video-based group counseling. The systematic and complete provision of information would facilitate the decision-making of adolescents, hence increasing the continuation rate of contraceptive implant.